PENGARUH LATIHAN KESEIMBANGAN DAN KELENTURAN TERHADAP KEMAMPUAN MOTORIK SISWA SEKOLAH DASAR - Laoli, Helpin Christin; Zalukhu, Petra Astrid Nauli; Hutasoit , Mikha Adonia Br; Pakpahan , Novaria; Sembiring , Heka (ASOSIASI IDEBAHASA KEPRI, 2025)
This community service activity aims to improve children's basic motor skills through balance and flexibility training at SD Negeri 080934. This training lasted for one day and was attended by fifth grade students as the main participants. The methods used included balance exercises such as walking on a straight line, standing on one leg, and playing with a balance board, plus flexibility exercises by doing fun muscle stretching in the form of group games. The evaluation showed a qualitative increase in students' motor skills. The active involvement of physical education teachers in this activity also showed the potential to continue this program into routine teaching and learning activities. In addition, this activity also helped develop students' cooperation and discipline values. It can be concluded that a balance and flexibility training program that is designed systematically and attractively has proven effective in supporting students' motor and character development. Further community service activities with a longer duration and quantitative evaluation are needed to strengthen these findings.